The Struggling Odyssey of Infantile Primary Hyperoxaluria - Guillaume, Adrien; Chiodini, Benedetta; Adams, Brigitte; Dahan, Karin; Deschênes, Georges; Ismaili, Khalid (Frontiers in Pediatrics, 2021)
Introduction: Oxalate overproduction in Primary Hyperoxaluria type I (PH1) leads to progressive renal failure and systemic oxalate deposition. In severe infantile forms of PH1 (IPH1), end-stage renal disease (ESRD) occurs in the first years of life. Usually, the management of these infantile forms is challenging and consists in an intensive dialysis regimen followed by a liver-kidney transplantation (combined or sequential). Methods: Medical records of all infants with IPH1 reaching ESRD within the first year of life, diagnosed and followed between 2005 and 2018 in two pediatric nephrology departments in Brussels and Paris, have been reviewed. Results: Seven patients were included. They reached ESRD at a median age of 3.5 (2-7) months. Dialysis was started at a median age of 4 months (2-10 months). Peritoneal dialysis (PD) was the initial treatment for 6 patients and hemodialysis (HD) for one patient. Liver transplantation (LT) was performed in all patients and kidney transplantation (KT) in six of them. A sequential strategy has been chosen in 5 patients, a combined in one. The kidney transplanted as part of the combined strategy was lost. Median age at LT and KT was 25 (10 to 41) months and 32.5 (26 to 75) months respectively. No death occurred in the series. At the end of a median follow-up of 3 years, mean eGFR was 64 29 ml/min/1.73m2. All patients presented retinal and bone lesions and five patients presented bones fractures. Conclusion: Despite encouraging survival figures, the morbidity in IPH1 patients remains extremely heavy and its management presents a huge challenge. Thanks to the newly developed RNA-interference drug, the future holds brighter prospects.